Effects of Corporate Governance on the Performance of Nepalese Firms - Silwal, Prem Prasad (The International Research Journal of Management Science, 2016)
The paper examines the effect of corporate governance on the performance of Nepalese firms. Return on assets, return on equity and Tobin’s Q are the dependent variable for firm performance and firm size, leverage, board size, age of the firm, and audit committee are the explanatory variables. Data are collected from annual report of 18 non financial firms listed in NEPSE from 2010 to 2015.The multiple regression models were estimated to test the effect of explanatory variables on firm performance. The result reveals that corporate governance has significant impact on firms’ performance based on return on assets. Board size, and leverage have negative and significant effect on firm performance however age of the firm and audit committee have positive effect on firm performance based on return on equity. While regressing firm performance based on Tobin’s Q, board size and audit committee are the major factors in determining the firm performance.